SOURCES OF RESISTANCE TO TOMATO LEAFMINER IN CHERRY TOMATO - SOBREIRA, Fábio Moreira; SOBREIRA, Fabricio Moreira; ANDRADE, Gilberto Santos; ALMEIDA, Gustavo Dias de; MATTA, Frederico de Pina (Scientia Agraria, 2009)
The tomato plant has narrow genetic base due to intensive breeding and domestication of wild varieties. On the other hand, accessions are a potential source of germplasm against insect pests for tomato crop. The aim of this study was to evaluate the injury caused by Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in the leaves and plant of Lycopersicon esculentum var. cerasiforme. The phenotypic and qualitative variability among 15 accessions, injury in leaves and plant after 20 days were evaluated. The injury in leaves and plant were carried out by the scale notes. In general, the accession CCAUFES 40 was the most resistant to T. absoluta, what indicate that one have potential as a source of germplasm for plants breeding of tomato against T. absoluta.